Innovative Leadership of Administrators Affecting Academic Administration in Schools under Bueng Kan Primary Educational Service Area Office - Nimma, Siriphum; Eungpuang, Arkom (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this study were 1) to study innovative leadership of administrators in schools under Bueng Kan Primary Educational Service Area Office. 2) to study academic administration in schools under Bueng Kan Primary Educational Service Area Office. And 3) to study the innovative leadership of administrators that affects academic administration in schools under Bueng Kan Primary Educational Service Area Office. The sample group consisted of administrators and teachers under Bueng Kan Primary Educational Service Area Office, with the total number of 343 people. The sample size was determined by using Taro Yamane formula at a sampling error level of 0.05, using school-based stratified random sampling method. The research instrument was a 5-level rating scale questionnaire with a reliability in each aspect of 0.93 and 0.94. The statistics used for data analysis comprised of frequency, percentage, mean, standard deviation, and stepwise multiple regression analysis. The research results were found that: 1. The innovative leadership of school administrators, in overall and each aspect, was rated at a high level. 2. Academic administration in schools, in overall and each aspect, was rated at a high level. and 3. Innovative leadership of school administrators in aspect of supporting and motivating personnel and creativity, which could forecast academic administration in schools together by 32.90 percent, with statistical significance at .01 level.